IMPLEMENTASI GENERAL ENTERPRISING TEST (GET2) DAN KONTRIBUSINYA UNTUK MENDORONG SISTEM EDUKASI GEN-Z INDONESIA BERDASARKAN LOCUS OF CONTROL - Yusrin, Nur Amalyna (Jurnal Bina Manajemen, 2023)
The world is not okay even the COVID-19 pandemic has passed. The global economy has experienced a sharp contraction since 2020. This has an impact on depreciation in household consumption which has an impact on decreasing people's welfare. The increase number of jobs is expected to be able to increase economic welfare for the Indonesian people affected by layoffs. However, the number of business in Indonesia is still low. Where the level of public awareness tendency to become entrepreneurs compared to intrapreneurs is still minimal. Education is one of the stakeholder to increase the awareness about the importance of building a business. Higher education as a scientific institution is required to be more innovative in carrying out the learning process. An integrated learning ecosystem is needed that suits Gen-Z as the growing Indonesian population. In this study, The General Enterprising Test (GET2) method was implemented to measure the dominant tendencies of 111 students as respondents. Based on research, the tendency of an internal locus of control is the main character by Gen-Z. By creating an appropriate ecosystem it will be able to increase the number of university graduates who become entrepreneurs.